A Review of Water Footprint Assessment in Water Services - Edriyana, Abd Aziz; Syazwan, N. Moni; Noraini, Yussof (2020)
This paper presents the review of water footprint assessment in water services. Water footprint assessment (WFA) is the study of freshwater use, scarcity, and pollution in relation to consumption, production, and trade. All living things require water to grow and reproduce. Therefore, it must be managed in a sustainable manner to ensure the social, economic and environmental development of the current and future generations are not affected. Recently, water shortages are increasingly reported compromising the sustainability of several large cities and regions worldwide. Some regions for instance Malaysia is currently facing water scarcity problem despite it has high quantity of water resources and for the last two decades Malaysia experienced warming and rainfall irregularities, thus this might implicate the problem. As the increase in future water demand will be mainly due to increased industrial water demand, managing industrial water use is considered as a major option to relief foreseen water stress. Asia will need on average 65% more freshwater withdrawals for their industry and energy sectors by 2030 to meet the forecasted national economic growth rate. To date in current literature, formulating response options to reduce unsustainable WFs has been underemphasized. A large gap and thus research opportunity remains in understanding dynamics of proposed measures or policy recommendations that effectively reduce WFs. From the review, there are reveal how to conduct more water footprint assessment on the services as it is pertinent to assess the sustainability of water resources in a basin. Water stewardship and integrated river basin management engage a range of stakeholders in finding solutions which reduce wasteful water use and implement good water governance.